Comparative plastome genomics and phylogenetic relationships of the genus Trollius - Li, Jiaxin; Du, Yan; Xie, Lei; Jin, Xiaohua; Zhang, Zhirong; Yang, Meiqing (Frontiers in Plant Science, 2023)
Trollius, a genus in the Ranunculaceae family, has significant medicinal and ornamental value. It is widely distributed in China with 16 different species accepted. However, due to the lack of enough samples and information sites, the molecular phylogenetic relationships of Trollius have been unresolved till now. Here we sequenced, assembled and annotated the plastomes of 16 Trollius species to investigate their genomic characteristics, inverted repeat (IR) boundaries, repeat sequences, and hypervariable loci. In addition, the phylogenetic relationships of this genus was reconstructed based on the whole plastomes and the protein-coding sequences data-sets. The plastomes of Trollius ranged between 159,597 bp and 160,202 bp in length, and contained 113 unique genes, including 79 protein coding, 30 tRNA, and 4 rRNA. The IR boundaries were relatively conserved within the genus Trollius. 959 simple sequence repeats and 657 long repeat sequences were detected in the Trollius plastomes. We identified 12 highly polymorphic loci (Pi > 0.0115) that can be used as plastid markers to molecular identification and phylogenetic investigation of the genus. Besides, Trollius was a monophyletic group with the earliest divergence clade being Trollius lilacinus Bunge, and the remaining species were divided into two strongly-supported clades. The phylogeny in our study supported the traditional classification systems based on the color of sepal, but not the previous classification system based on the types and relative lengths of the nectaries, and distribution. The genomic resources provided in our study can be used in the taxonomy of the genus Trollius, promoting the development and utilization of this genus.